2016
DOI: 10.1039/c6ra15267h
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature fabrication of a three-dimensional reduced-graphene oxide/polypyrrole/hydroxyapatite composite scaffold for bone tissue engineering

Abstract: The development of tissue engineering (TE) provides a promising alternative strategy for bone healing and regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 58 publications
1
40
0
Order By: Relevance
“…In some studies, the rGO/HA grafts have been shown to enhance new bone formation to a significant extent in rabbit calvarial detects, without introducing any sign of inflammatory responses . Encouraged by the excellent capability of rGO to enhance the performance of bioceramics‐based scaffolds, rGO have also been used as a filler to improve the functions of polymer‐based, or composites of polymers and bioceramics‐based scaffolds . Selective examples regarding the applications of rGO in BTE are summarized in Table .…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
“…In some studies, the rGO/HA grafts have been shown to enhance new bone formation to a significant extent in rabbit calvarial detects, without introducing any sign of inflammatory responses . Encouraged by the excellent capability of rGO to enhance the performance of bioceramics‐based scaffolds, rGO have also been used as a filler to improve the functions of polymer‐based, or composites of polymers and bioceramics‐based scaffolds . Selective examples regarding the applications of rGO in BTE are summarized in Table .…”
Section: Carbon‐based Nanomaterials For Bone Tissue Engineeringmentioning
confidence: 99%
“…In a previous study, we successfully fabricated a 3D rGO/PPY scaffold with good osteogenic performance through a simple electrostatic LBL assembly strategy, followed by an electrochemical deposition process using nickel foam as a template. 8 The prepared 3D rGO/PPY scaffold demonstrated good mechanical properties with hardness of 92.27 AE 4.03 MPa and Young's modulus of 185.94 AE 10.76 MPa. 8 Unfortunately, the 3D rGO/PPY scaffold does not have enough biological activity.…”
Section: Preparation and Characterization Of The Cpp-modied 3d Rgo/pmentioning
confidence: 99%
“…8 The prepared 3D rGO/PPY scaffold demonstrated good mechanical properties with hardness of 92.27 AE 4.03 MPa and Young's modulus of 185.94 AE 10.76 MPa. 8 Unfortunately, the 3D rGO/PPY scaffold does not have enough biological activity. Considering the intriguing calcium binding properties of CPP molecules, in the present study, we assembled the CPP molecules on the developed 3D rGO/PPY scaffold and explored the application of the composite scaffold in bone tissue engineering.…”
Section: Preparation and Characterization Of The Cpp-modied 3d Rgo/pmentioning
confidence: 99%
See 2 more Smart Citations